A framework to model the key performance indicator for information technology strategic planning - Jusoh, Yusmadi Yah; Hamdan, Abdul Razak; Deraman, Aziz (2005)
This paper examines the issues concerning the implementation of the information technology (IT) strategic plans. From the literature, strategic planning for IT is fundamental to ultimate effectiveness of the plan implementation. In order to improve the successfulness of the IT strategic planning implementation, a framework is presented to describe and associate general plans contents: mission, goal and strategic objectives with the suggested key performance indicators. The framework concept and list of key performance indicators are illustrated by modeling the real case example of IT strategic planning documents.